Use of a new micropattern tape method to detect chirality shifts in differentiating C2C12 cells - Qingkai Weng; Takashi Osaka; Hiroaki Onoe; Koki Yoshida; Yukiko Kuroda; Koichi Matsuo; Katsuhiro Kawaai (PLoS ONE, 2025)
Chirality is an intrinsic property of cells manifested as left-right (LR) asymmetry in terms of cellular morphology and organization, which influences cell behavior, migration, and tissue development. Traditional in vitro methods used to study cell chirality often require complex fabrication methods, limiting their accessibility and reproducibility. Here, we present a novel micropattern tape method that facilitates fabrication of high-quality rectangular micropatterns useful for efficient, high-throughput analysis of cell chirality. Using this method, we characterized chirality of C2C12 myoblasts and MC3T3-E1 osteoblasts, which respectively exhibit clockwise (CW) and counterclockwise (CCW) chirality relative to the long axis of the rectangle. We used the method to analyze how cellular differentiation impacts chirality and observed striking reversal of C2C12 cell chirality upon bone morphogenic protein-2 (BMP2)-induced osteoblastic differentiation. These results demonstrate that our micropattern tape method can effectively detect dynamic change of cell chirality during differentiation.